Etnoictiologia de pescadoras e pescadores artesanais: fortalecimento e valorização dos conhecimentos tradicionais, na comunidade de Espírito Santo do Tauá – PA - BARBOSA, Adenilse Borralhos (2021)
This plan of action aims to subsidize the construction of the Ethnoicological didactic book of the School of the community of Espírito Santo do Tauá, and thus to visualize the traditional knowledge and local knowledge of fisherwoman and artisanal fishermen; from this didactic book we aim to develop training workshops with community and subjects of the school space.The community is located on the highway PA 242 in the municipality of Santo Antônio do Tauá, Nordeste Paraense. The work is one of the strategies to consolidate the knowledge, skills and knowledge of fisherwoman and artisanal fishermen in the Municipal School of Primary Education Francisco Solano Rayol Pereira, through the ethnoictiological didactic book that was built collectively from the methodological process of action research. This booklet aims to contribute to teachers, students and members of the school community understand the economic, political, social and cultural diversity, including ethnoictiology of artisanal fisherwoman and fishermen of the river Tauá. The didactic book will be an instrument of paramount importance to the knowledge of learners and also to strengthen and enhance the fishing activity within the school space. This didactic book will be made available and used in the community school, with a view to the dialogue on local socio-biodiversity, traditional knowledge and practices, in the disciplines of Sciences and Geography.